TSG-6 treatment promoted apoptosis in human fibroblasts of pathological scar - Wang, H; Chen, Z; Li, X; Tang, Y; Li, X; Zhang, S; Ma, L; Huang, X (Cellular and Molecular Biology, 2016)
Pathological scars are characterized by excessive fibrosis and extracellular matrix (ECM) deposition and can be functionally and cosmetically problematic; however, there are few satisfactory treatments for controlling pathological scars. The proliferation of fibroblast during wound healing play an important role in pathologic scar formation. Therefore, the promotion of fibroblast apoptosis may be a new point to inhibit scar formation. In this study, pathological scar fibroblasts were treated with TSG-6 in monolayer culture and subjected to examination for cell apoptosis and associated proteins involved in cell apoptosis. We found that TSG-6 significantly promoted cell apoptosis of pathological scar fibroblasts. Meanwhile, expression level of cell apoptosis related cytokine protein Bax increased and cell proliferation related signal transduction pathways are blocked since the expression level of Bcl-2 was decreased.